LH level on trigger day, number of follicles ≥16 mm but <18 mm, and number of retrieved oocytes are independent risk factors for polyspermy in gonadotropin-releasing hormone antagonist protocol - Wu, Qiongyu; He, Lina (Frontiers in Endocrinology, 2024)
IntroductionThe polyspermy rate is a quality control indicator in the embryology laboratory, and factors affecting polyspermy are of great interest. The gonadotropin-releasing hormone (GnRH) antagonist protocol is currently the mainstream protocol in most reproductive centers. This study explored the factors influencing polyspermy in in vitro fertilization (IVF) using the GnRH antagonist protocol and considered corresponding improvement measures.MethodsThis retrospective case-control study analyzed 354 patients who underwent conventional IVF with a GnRH antagonist protocol at Zigong Maternal and Child Health Hospital from November 2019 to September 2023. Patients were divided into two groups based on the occurrence of polyspermy, and baseline characteristics and clinical data were compared between the groups. Variables with P<0.05 in univariate logistic regression were included in the multivariate logistic regression model. Cutoff values for variables with P<0.05 were calculated.ResultsMultivariate logistic regression corrected for confounding factors identified that luteinizing hormone (LH) level on trigger day, the number of follicles ≥16 mm but <18 mm, and the number of retrieved oocytes were significantly associated with polyspermy (OR=1.305, P=0.005; OR=1.235, P=0.002; OR=1.101, P<0.001, respectively). The cutoff values were 1.95 IU/L, 4.5 follicles, and 16.5 oocytes, respectively.ConclusionIn the GnRH antagonist cycle, LH level on trigger day, the number of follicles ≥16 mm but <18 mm, and the number of retrieved oocytes are independent risk factors for polyspermy. When LH level on trigger day exceeds 1.95 IU/L, the number of follicles ≥16 mm but <18 mm exceeds 4, and the number of oocytes retrieved exceeds 16, the risk of polyspermy increases significantly.